Aplikasi Handling Problem Unit IT Infrastruktur Divisi Teknologi Dan Sistem Informasi Pada Bpd Sumsel Babel Berbasis Website - Faradillah; Susilo, Darmawan; Di Kesuma, Hendra (Jurnal Ilmiah Binary STMIK Bina Nusantara Jaya, 2023)
The Regional Development Bank (BPD) of South Sumatra and Bangka Belitung (Sumsel Babel) is a financial institution with a complex and important IT infrastructure system in its operations. The purpose of this research is to develop an application that can help in handling these problems. The method used in this research is the waterfall method which consists of requirements analysis, design, implementation, testing, and maintenance. The proposed solution design is a website-based problem handling application. This application will provide access to the IT Infrastructure Team to submit problem reports and monitor repair status in real-time. Additionally, this application will also be equipped with user management features, access rights management, and notification systems that will inform users of repair status. It is hoped that with this application, the efficiency and effectiveness of IT infrastructure problem handling can be better, thus speeding up response time in problem solving and increasing customer satisfaction. In conclusion, the use of website-based problem handling applications at the Regional Development Bank (BPD) of South Sumatra and Bangka Belitung (Sumsel Babel) can help improve the performance of the IT infrastructure unit of the Technology and Information Systems Division, thereby expected to better meet user needs.